Analisa Penjadwalan Produksi Dengan Metode Campbell Dudek Smith Untuk Meminimasi Makespan di CV. YZX - Muhammad Taufiq; Endang Pudji Widjajati (Pusat Riset dan Inovasi Nasional, 2023)
CV YZX is a manufacturing company in the stainless steel hardware sector that specializes in hardware and detailing. This company actively produces for the needs of individual consumers and orders from other companies. One of the problems faced by CV YZX is the use of production machines that are less than optimal at every stage of the production process. Production machine performance that is not optimal can increase the total value of production time (makespan), which in turn can cause delays in completing products and delivery to consumers. This research aims to find the minimum total production time value by applying the Campbell Dudek Smith method to production scheduling. The calculation results show that by applying the First Come First Serve (FCFS) production scheduling method, the company obtained a makespan of 39.64 hours. However, by using the proposed method, namely Campbell Dudek Smith (CDS) in production scheduling, the results of the makespan calculation show a figure of 33.58 hours. A comparison of the two methods shows that the proposed scheduling using the Campbell Dudek Smith method has a lower makespan value compared to the company method (FCFS), resulting in time savings of 6.06 hours or the equivalent of 15,3%.